Pengembangan Media Papan Smart Subtraction Bag Sebagai Upaya untuk Menigkatkan Motivasi Belajar Siswa Kelas 1 Sekolah Dasar - Yulia Eka Yanti (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to produce a smart subtraction bag board media that is feasible, valid to use in learning subtraction materials, and can increase student learning motivation through the implementation of smart subtraction bag board media so that learning is more effective, interesting, and can help students' rapidity and accuracy in the counting process. The type of research used is RnD (Research and Development) with the Thiagarajan 4D development model which consists of four stages: (1) define; (2) design; and (3) the development and the dissemination stage (not done). The instruments used in this study were a motivation questionnaire and a product validation sheet. The research subjects were 1ˢᵗ grade elementary school students with 2 stages, namely individual trials with 5 students and small group trials with 7 students with heterogeneous abilities previously seen from daily value data. Based on the results of the research conducted, it was obtained a percentage of 93,7% media experts, 86,6% scores from material experts, student responses in individual trials obtained a percentage of 100%. While the results of the questionnaire on student learning motivation in small group trials before using the media obtained 30% after using the media obtained 82%. This shows that students' learning motivation increased until 52% for the very high category. Based on the results of research that has been carried out, some suggestions can be conveyed, namely optimizing the use of media so that students are more motivated in learning.